2013
DOI: 10.1158/1078-0432.ccr-11-1446
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to BRAF Inhibition in BRAF-Mutant Colon Cancer Can Be Overcome with PI3K Inhibition or Demethylating Agents

Abstract: Purpose Vemurafenib, a selective inhibitor of BRAFV600 has shown significant activity in BRAFV600 melanoma, but not in the <10% of metastatic BRAFV600 colorectal cancers (CRC), suggesting that studies of the unique hypermethylated phenotype and concurrent oncogenic activation of BRAFmut CRC may provide combinatorial strategies Experimental Design We performed comparative proteomic analysis of BRAFV600E melanoma and CRC cell lines, followed by correlation of PI3K pathway activation and sensitivity to the vemu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
210
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(232 citation statements)
references
References 48 publications
13
210
0
Order By: Relevance
“…K-ras and BRAF mutations were linked with activation of AKT and ERK signaling pathway. [19][20][21][22][23][24] Therefore, the involvement of AKT and ERK activation in the increase of Bcl-2 expression can be expected in colorectal cancer. All cell lines used in this study harbored either K-ras mutation or BRAF mutation (Supplementary Figure 7a).…”
Section: Discussionmentioning
confidence: 99%
“…K-ras and BRAF mutations were linked with activation of AKT and ERK signaling pathway. [19][20][21][22][23][24] Therefore, the involvement of AKT and ERK activation in the increase of Bcl-2 expression can be expected in colorectal cancer. All cell lines used in this study harbored either K-ras mutation or BRAF mutation (Supplementary Figure 7a).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo xenograft models have shown that colorectal carcinoma that harbor BRAF V600E may be sensitive to proteasome inhibitors (14). Although colorectal carcinomas have very limited response to BRAF V600E inhibitor monotherapy (15,16), combinatorial strategies are currently under investigation to improve response, and outcome for these patients (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Drugs available against other RAS-regulated signaling proteins, such as BRAF and MEK, have also shown moderate efficacy, although this is limited due to rapid development of acquired resistance, in many cases due to aberrant activation of parallel signaling pathways that in turn stimulate the PI3K pathway (8)(9)(10). Moreover, RAS itself has proved impossible to target effectively to date (11,12).…”
Section: Introductionmentioning
confidence: 99%